2020
DOI: 10.3390/biomedicines8110462
|View full text |Cite
|
Sign up to set email alerts
|

miR-98 Regulates TMPRSS2 Expression in Human Endothelial Cells: Key Implications for COVID-19

Abstract: The two main co-factors needed by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to enter human cells are angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2). Here, we focused on the study of microRNAs that specifically target TMPRSS2. Through a bioinformatic approach, we identified miR-98-5p as a suitable candidate. Since we and others have shown that endothelial cells play a pivotal role in the pathogenesis of the coronavirus disease 2019 (COVID-19), we mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 84 publications
1
126
0
Order By: Relevance
“…To identify miRNAs targeting the 3′-UTR of Neuropilin-1, we used the online target prediction tool Targetscan 7.2, as previously described by our research group [ 28 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify miRNAs targeting the 3′-UTR of Neuropilin-1, we used the online target prediction tool Targetscan 7.2, as previously described by our research group [ 28 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effects of miR-24 on Neuropilin-1 gene transcription, we used a luciferase reporter containing the 3’-UTR of the predicted miRNA interaction site, both wild-type and mutated, in hBMECs cells. The mutant construct of Neuropilin-1 3′-UTR (Neuropilin-1 MUT, as shown in Figure 1 ), harboring a substitution of two nucleotides within the predicted miR-24 binding sites of Neuropilin-1 3′-UTR was obtained through means of the NEBaseChanger and Q5 site-directed mutagenesis kit (New England Biolabs, Ipswich, MA, USA) as we described [ 30 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it has been shown that endothelial involvement is associated with microvascular thrombi and prothrombotic state in patients with COVID-19. [28][29][30] Also, in a series of infected patients with SARS-COV2, evidence has been reported of direct viral infection of the endothelial cell and diffuse endothelial inflammation. 31 The current study revealed that a high level of infection-induced inflammation at the time of admission predicts a poor prognosis in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, host miRNAs might block attachment and entry of SARS-CoV-2 because several miRNA families were found to target ACE2 and TMPRSS2 genes in different tissues. In an in vitro study, hsa-miR-98-5p was demonstrated to directly target the 3' UTR of TMPRSS2 gene transcription, both in human lung microvascular endothelial cells (HMVEC-L) and human umbilical vein endothelial cells (HUVEC) [29]. The hsa-let-7e/hsa-mir-125a and hsa-mir-141/hsa-miR-200 miRNA families inhibit ACE2/TMPRSS2 gene transcription.…”
Section: Attachment and Entrymentioning
confidence: 99%